Public Understanding and Their Response to Covid-19 in Nepal: A Population Based Study - Ghimire, Rakesh; Adhikari, Bidur; Pokharel, Akritee; Subedi, Ranjeeta; Shakya, Sujata; Khapung, Anju; Kharel, Shristi; Bhandary, Shital; Gyanwali, Pradip (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: : Corona Virus Disease (COVID-19) pandemic has become one of the major causes of death. Its prevention and control have been challenging for every nation. Public understanding and practice play vital roles in its containment. This study aimed at identifying public understanding and response to COVID-19 in Nepal.Method: : A population-based, cross-sectional study was conducted in Nepal among 3,582 adults through an online, self-administered questionnaire shared via Viber group created by Ministry of Health and Population. The outcome variables measured were knowledge, attitude and practice regarding COVID-19. The responses were analysed and predictors of response studied.Results: Most of the participants were male (73.2%), with mean age of 32.4 years. Majority were married (54.2%) and had knowledge about transmission and symptoms of COVID-19. Almost all (99.6%) stated that hand washing/sanitizing can prevent its transmission. However, myths about prevention like drinking hot water (78.9%), gargling (67.6%), avoiding imports (67.6%), distancing from pets (65.6%), and warm showers (40%) were prevalent. Most of the participants (98%) used mask. The average knowledge score was 9.74±1.59 out of 12, attitude score 7.09±0.77 out of 8, and practice score 2.70±0.53 out of 3. Majority supported the government’s efforts but were facing problems like difficulty getting daily consumables, increased levels of mental illnesses due to confinement, and facing increased economic burdens because of lockdown.Conclusion: From the findings, we can infer that government interventions should focus on minimizing the public’s difficulties due to lockdown while enforcing prevention strategies via raising awareness about COVID-19.